EFEKTIVITAS TAX AMNESTY DI INDONESIA: STUDI META-ANALISIS - Mamesah, Joshua Jordan; Kristanto, Ari Budi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.05.TAHUN.2021DO - 10.24843/EEB.2021.v10.i05.p04, 2021)
This study aims to examine whether the tax amnesty program implemented in 2015 can improve individual taxpayer compliance in Indonesia. This study uses a meta-analysis approach to synthesize the results of previously conducted research to evaluate the benefits of the tax amnesty policy. The results of this study indicate evidence that the tax amnesty program has a positive effect on individual tax compliance so that it is concluded that the implementation of the tax amnesty program is considered effective in increasing individual tax compliance. Theoretically, this research enriches the literature and provides conclusions for the results of previous studies. The results of this study can be used by the Government of Indonesia in evaluating the impact after this tax amnesty policy ends.